2020
DOI: 10.3389/fmolb.2020.584053
|View full text |Cite
|
Sign up to set email alerts
|

PAXX, Not NHEJ1 Is an Independent Prognosticator in Colon Cancer

Abstract: Classical Non-homologous End Joining (NHEJ) pathway is the mainstay of cellular response to DNA double strand breaks. While aberrant expression of genes involved in this pathway has been linked with genomic instability and drug resistance in several cancers, limited information is available about its clinical significance in colon cancer. We performed a comprehensive analysis of seven essential genes, including XRCC5, XRCC6, PRKDC, LIG4, XRCC4, NHEJ1, and PAXX of this pathway, in colon cancer using multi-omics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Even though the underlying mechanism was not quite known, it was suggested that PAXX may be involved in some proto-carcinoma signaling pathways through its function beyond DNA repair. Meanwhile, there is a correlation between the overexpression of PAXX and the survival rate of patients, and the expression of PAXX may be used as a prognostic marker for disease-specific survival ( 95 ).…”
Section: Paxx and Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the underlying mechanism was not quite known, it was suggested that PAXX may be involved in some proto-carcinoma signaling pathways through its function beyond DNA repair. Meanwhile, there is a correlation between the overexpression of PAXX and the survival rate of patients, and the expression of PAXX may be used as a prognostic marker for disease-specific survival ( 95 ).…”
Section: Paxx and Cancer Developmentmentioning
confidence: 99%
“…Interestingly, in OS cells that are resistant to doxorubicin or cisplatin, the expression of PAXX was upregulated, and when PAXX was knocked out or specifically inhibited, drug sensitivity was restored. In this scenario, PAXX might be used as a target to effectively promote the effects of chemotherapy drugs ( 95 ). In addition, for tumors with XLF mutations, we could inhibit PAXX,which has less damage to the body after knockdown, as adjuvant therapy.…”
Section: Paxx and Cancer Developmentmentioning
confidence: 99%
“…Their protein complex could bind to DNA and be involved in DNA repair and transcription of selected genes, such as ERBB2 [23]. Similar differences in the correlation of the complex component abundances at protein and transcription level were also apparent in the colon cancer [24]. Therefore, phenotype-related functions may be better reflected at the protein level.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] Interestingly, it was recently documented that C9orf142 is highly expressed in colon cancer tissues due to its promoter hypo-methylation and acts as an independent prognosticator in colon cancer. 19 In addition, C9orf142 is up-regulated in chemoresistant osteosarcoma 20 and glioma 21 cells. Interestingly, examination of our recently released TNBC proteomic 22 and transcriptomic 23 datasets reveals that C9orf142 is markedly increased in TNBC tissues and has a positive correlation with lymph node metastasis of TNBC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from mouse model studies indicates that C9orf142 is a compensatory factor in the development of central nervous and immune systems, 14,15 and that combined deficiency of C9orf142 and XRCC4‐like factor (XLF) results in embryonic lethality 16‐18 . Interestingly, it was recently documented that C9orf142 is highly expressed in colon cancer tissues due to its promoter hypo‐methylation and acts as an independent prognosticator in colon cancer 19 . In addition, C9orf142 is up‐regulated in chemoresistant osteosarcoma 20 and glioma 21 cells.…”
Section: Introductionmentioning
confidence: 99%